Tarantula Bite in Iran, a Letter to the Editor - Sanaei Zadeh, Hossein (Archives of Academic Emergency Medicine, 2018)
I read with great interest the case report titled â€œPeriumbilical pain with radiation to both legs following tarantula bite; a case reportâ€ published in Emergency journal.Â Tarantula spiders are not medically important except for some very limited species, which do not exist in Iran. Solifugae -orÂ rotailsÂ as they are called in Iran- are in fact another group of animals also called camel spiders (Figure 2). They are also venom-free and generally cause secondary infections in the site of their bites. Thus, it seems that the patient’s signs and symptoms cannot be due to the rotail or tarantula bites.